Knowledge and Attitude Regarding Pubertal Health among Adolescent Girls - Dhakal, Binita (Journal of Nepal Health Research Council, 2020)
Background: Adolescence is a critical period and is associated with physical and psycho-social changes induced by puberty, which builds personality, behaviour, and future health of the adolescents. Thus, the aim of the study was to find out the knowledge and attitude regarding pubertal health of adolescence girls.Methods: A descriptive cross sectional study was conducted in Bharatpur Metropolitan City’s secondary level schools. A total of 183 adolescent girls were selected using probability simple random sampling from 5 schools out of total 43 schools which were also selected by simple random sampling technique. Data was collected by using structured self-administered questionnaire for knowledge and likert’s scale was used for attitude regarding pubertal health. Results: Study findings revealed that 61.4% of the students belonged to early adolescence (11-14) age group with the mean age 14.27±1.33 years. Majority (80.3%) had moderate level of knowledge and around half (48.6%) had positive attitude. Knowledge and attitude varied with the respondents’ level of education (p=0.001), relation to sibling (p=0.013) and source of information by elder sister (p=0.022), teachers/school (p=0.001).Moderately positive correlation was found between knowledge and attitude which was highly significant (r=0.395, p<0.001).Conclusions: Majority of respondents had moderate level of knowledge and half of the respondent had positive attitude regarding pubertal health. Findings of the study emphasizes on improvement in education of adolescent girls which can help uplift health status and minimize vulnerability to health issues of pubertal health. Keywords: Adolescents; attitude; knowledge; pubertal health; puberty.